NCX-1015, a nitric-oxide derivative of prednisolone, enhances regulatory T cells in the lamina propria and protects against 2,4,6-trinitrobenzene sulfonic acid-induced colitis in mice - Fiorucci, Stefano (National Academy of Sciences, 2002)
NCX-1015 is a nitric oxide (NO)-releasing derivative of prednisolone. In this study we show NCX-1015 protects mice against the S. A. development and induces healing of T helper cell type 1-mediated experimental colitis induced by intrarectal administration of 2,4,6-trinitrobenzene sulfonic acid (TNBS). The beneficial effect of NCX-1015 was reflected in increased survival rates, improvement of macroscopic and histologic scores, a decrease in the mucosal content of T helper cell type 1 cytokines (protein and mRNA), and diminished myeloperoxidase activity in the colon. In contrast to its NO derivative, only very high doses of prednisolone were effective in reproducing these beneficial effects. NCX-1015 was 10- to 20-fold more potent than the parent compound in inhibiting IFN-γ secretion by lamina propria mononuclear cells. Protection against developing colitis correlated with inhibition of nuclear translocation of p65/Rel A in these cells. In vivo treatment with NCX-1015 potently stimulated IL-10 production, suggesting that the NO steroid induces a regulatory subset of T cells that negatively modulates intestinal inflammation.